THE EFFECT OF COMMUNICATION ON THE IMPLEMENTATION OF THE POLICY FOR THE UTILIZATION OF JKN CAPITATION FUND AT THE BARANA HEALTH CENTER JENEPONTO REGENCY - Zilfadhilah Arranury (Universitas Islam Negeri Alauddin Makassar, 2022)
Background: Capitation is a payment method for health services in the context of providing and improving quality and measurable health services including health services, primary health care operational costs and procurement of health infrastructureObjective: This study aims to determine the effect of communication on the implementation of the JKN Capitation Fund Utilization Policy at the Barana Health Center, Jeneponto RegencyMethod: This research method was descriptive with a qualitative approach. Data were obtained by means of In-depth Interview, documentation, and Observation to all informants selected by Purposive Sampling.Result: The results of the study showed that communication in disseminating information regarding policies for the use of JKN capitation funds at the Barana Health Center has been going well, clearly and consistently. The obstacles that are sometimes encountered in the implementation of these policies when replacing JKN managers.Conclusion: Communication Mechanism for the use of JKN capitation funds at the Barana Health Center, Jeneponto Regency has been running according to the procedure but has not run optimally. Therefore, the Jeneponto District Health Office is expected to continue to monitor the management of policies on the use of JKN capitation funds.